FORWARD AND BACKWARD TRANSLATION OF THREE DIFFERENT WORD CLASSES BY EARLY-SEQUENTIAL SUNDANESE-INDONESIAN BILINGUALS - Munir, Ade Abdul (2016)
This study entitled "Forward and Backward Translation of Three Different Word Classes by Early-Sequential Sundanese-Indonesian Bilinguals"investigated the performance of early-sequential Sundanese-Indonesian bilinguals in performing translation production test in either forward or backward direction of translation. In an attempt to answer the formulated research question, this present study employed the model or devise called Number of Translation (NOT) effects proposed by Tokowicz et al (2002). A translation production test was carried out in order to test 30 early-sequential Sundanese-Indonesian bilinguals, consisting of 15 female and 15 male participants, participating in this study. This study employed quantitative design, particularly descriptive statisticsas well as document analysis. The findings then revealed that the majority of early-sequential Sundanese-Indonesian bilinguals performed better in forward translation than in backward translation. In addition to this, the results of the word class analysis also indicated that all three different word classes were translated more accurately in forward translation than in backward translation. Furthermore, based on the gender analysis, male participants resulted in higher accurate answers in either forward or backward translation.